A study on echocardiography findings in severe pre-eclampsia and their maternal and fetal outcome - C., Nandhini C.; C, Raji; Priyaa P., Lakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Pre-eclampsia includes elevated blood pressure after 20 weeks of gestation with proteinuria. It constitutes the major reason behind maternal mortality in developing countries. It is one of the major reasons of maternal mortality and morbidity having greater effect on fetal morbidity and mortality also. The objectives of the study were to study the echocardiography changes in severe pre-eclampsia; to determine the left ventricular (LV) dysfunction in pre-eclamptic women by measuring the LV systolic and diastolic indices using echocardiography; to compare normal and abnormal ECHO findings in severe pre-eclampsia in terms of maternal and perinatal outcome. Methods: Prospective observational study conducted in department of obstetrics and gynaecology, Government Theni medical college from August 2019 to October 2020 to study normal and abnormal echocardiography changes in severe pre-eclamptic patients and to study maternal and fetal outcome in those two groups. Results: LV systolic function was within normal limits in our control and study group population of severe pre-eclampsia. Statistically significant LV diastolic dysfunction was seen Pulmonary edema and cardiac failure did not occur in any patient of our study population. Conclusions: From our study of ECHO in severe pre-eclampsia patients we came to a conclusion that left ventricular dysfunction occurs in many of the patients with severe pre-eclampsia and identification of diastolic dysfunction at an early stage could be of much use in preventing the complication which can arise due to the cardiac problems.